Flow Cytometry in the Diagnosis of Canine T-Cell Lymphoma - Comazzi, Stefano; Riondato, Fulvio (Frontiers in Veterinary Science, 2021)
T cell lymphoma (TCL) is a heterogenous group of lymphoid malignancies representing about 30-40% of all canine lymphomas and often harboring a very aggressive behavior. WHO classification identifies the majority of TCLs as peripheral T cell lymphoma but other sutbtypes with peculiar presentation and outcome have been recognized. This review aims to explore the use of flow cytometry for refining the diagnosis of canine TCL, with particular emphasis on the identification of some peculiar immunotypes, such as T zone lymphoma, the investigation of putative prognostic markers, and the evaluation of lymphoma stage and of minimal residual disease.